Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.15288/jsad.2015.76.68
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Behaviors and Life Course Socioeconomic Status During the Transition From Adolescence to Adulthood Among Whites and Blacks

Abstract: ABSTRACT. Objective:This study sought to determine how socioeconomic status (SES) changes during the transition from adolescence into adulthood, and to understand the effects of SES on drinking behaviors in early adulthood among U.S. Whites and Blacks. Method: Secondary data analysis was conducted using three waves of the National Longitudinal Study of Adolescent to Adult Health (Add Health), a school-based sample of adolescents (Grades 7-12) followed through adulthood (age range: 25-31 years). Through latent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…Our finding that higher socio-economic status increases the likelihood of low-risk drinking as opposed to abstaining is consistent with studies of older adults' alcohol consumption [18,23]. It suggests that further education and greater financial means are associated with a social position where drinking is potentially more affordable and where moderation is socially acceptable [35,36]. Drinking behaviour is widely considered to be agerelated, and often characterised by heavier episodic drinking during early adulthood, more frequent but lower overall consumption in mid-to-late adulthood [11,37], followed by increased prevalence of abstinence in later life [23].…”
Section: Discussionsupporting
confidence: 87%
“…Our finding that higher socio-economic status increases the likelihood of low-risk drinking as opposed to abstaining is consistent with studies of older adults' alcohol consumption [18,23]. It suggests that further education and greater financial means are associated with a social position where drinking is potentially more affordable and where moderation is socially acceptable [35,36]. Drinking behaviour is widely considered to be agerelated, and often characterised by heavier episodic drinking during early adulthood, more frequent but lower overall consumption in mid-to-late adulthood [11,37], followed by increased prevalence of abstinence in later life [23].…”
Section: Discussionsupporting
confidence: 87%
“…A very heterogeneous picture of results coming from the various longitudinal studies emerged. Results of several studies suggested that higher family SEP was associated with higher levels of health-promoting behaviour37 43 45 57 65 74 75 and lower levels of health-damaging behaviour. However, two studies pointed in the opposite direction 58 76.…”
Section: Discussionmentioning
confidence: 99%
“…The no drinking findings are in line with studies in EA populations in Britain, France, the US and Australia. [36][37][38][39] The reasons for the association between lower SES and not drinking are not well understood, although pre-existing poor physical or mental health may influence lifetime abstention. 36 It is increasingly recognized that EAs are drinking less than ever before, yet few population studies include nondrinking EAs as a subject of analysis.…”
Section: Ses No Hed and No Drinking In Emerging Adultsmentioning
confidence: 99%